Determination of Quality of Parboiled Rice by Adapting Different Processing Practices in Jaffna Peninsula - Prabhaharan, M.; Alvaappillai, P. (University of Jaffna, 2016)
Parboiling is a hydrothermal treatment applied before milling in order to increase milling recovery by minimizing broken rice percentage in the end product. Parboiling has three stages namely soaking, steaming and drying. Soaking and steaming play a key role to harden paddy grains by changing physical properties. Therefore, quality determination of end product is important. Effect of soaking and steaming duration on rice quality was investigated with respect to parboiling process. One kilogram of paddy was taken as sample. There were five treatments assigned with three replicates such as un-soaking and un-steaming, soaking and un-steaming, soaking and steaming an hour, soaking and steaming 2 hours soaking and steaming 3 hours. Soaking duration 12 hours at 30 oC was kept constant for all treatments. Machines were used on husking, milling and polishing of rice for analytical grade to evaluate the percentages of de-husked yield, head rice yield and broken rice yield, respectively. Lab scale detectors were used to count the quality attributes of white belly, heat damaged grains and whiteness value, which reflected the appearance of final processed product in local markets. Among the treatments, higher yield of dehusking rice, milling rice recovery and less percentage of broken rice were 78.4 %, 65.18 % and 11.9 %, respectively and obtained from the treatment of soaking 12 hours at 30 oC and steaming 2 hours of duration. The results revealed that steamed with two hours duration had given very less white belly, whereas un-soaked steamed rice kernel had highest percentage of white belly. The percentage of damaged grains by heat increased with the increasing the duration of steaming. There was significant difference on degree of de-husking, milling and broken percentage at 5% alpha level among treatments in un-soaked, un-steamed, soaked-un-steamed and soaked-steamed. Sample of Un-soaked with un-steamed had highest whiteness value while soaked with steamed samples yielded lowest whiteness values From these results, it can be concluded that the parboiling process has to be designed with soaking and steaming strategies to minimize the percentage of broken rice at the end product.
Keywords: Brown Rice Parboiling; Bulk soaking; Cottage milling; Traditional steaming